Resting Behaviour of Zika and Dengue Vector Aedes Aegypti Mosquito in Gia Lai, Viet Nam - Do, Van Nguyen; Nguyen, Xuan Quang; Huynh, Hong Quang; Ho, Van Hoang; Tran, Thanh Son; Nguyen, Thi Mong Diep (International Journal of Scientific Research in Biological Sciences, 2020)
The study was conducted in Pleiku city and Dak Po district belonging to Gia Lai province during the period 2016-2018. The results showed that Aedes aegypti was found in all study sites. The distincly anthropophilic and endophilic behaviours of Aedes aegypti make it a very effective vector of Dengue, Chikungunya, and Zika viruses. In total, 95.3% of 746 resting adult Ae. aegypti were collected indoors, and only 4.7% outdoors. Indoor primary resting locations (73.8%) included living rooms (13.9%), bathrooms (4.8%), and others (7.5%). In Pleiku city, most of Ae. aegypti adults were collected on nets/ curtains (164 mosquitoes, 53.2%), followed by clothes (30.2%) and the lowest on wall surfaces (0.3%). Similarly, in Dak Po district, total of 422 specimens were collected and the highest collection was on clothes surfaces (234 mosquitoes, 53.4%), followed by nets/ curtains (176 mosquitoes, 40.2%) and the lowest on television surfaces (0.7%). In all sites, Ae. aegypti significantly rested from 1-2 m of height (72.3%).